Destructive Role of COVID-19 Fear on Nurses Performance: Mediating Role of Stress - Zahid Yousaf; Abdelmohsen A. Nassani; Mohamed Haffar (MDPI AG, 2021)
Given its importance to psychological issues, the COVID-19 pandemic has created numerous challenges for all individuals, but healthcare professionals and particularly nursing staff are at front lines, and their performance is significantly affected. The current study relates COVID-19 fear with psychological strain, i.e., stress amongst the nursing staff. Moreover, the intervening role of COVID-19 stress between COVID-19 fear and the performance of the nursing staff has also been tested. An online survey was conducted to collect data from nurses. A total of 471 responses of nurses were received during the process of online data collection from 16 November 2020 to 30 April 2021. Results revealed the significant effect of COVID-19 fear on COVID-19 stress and the performance of nurses. Additionally, the results substantiate that COVID-19 stress mediates between COVID-19 fear and the health care performance of nurses. COVID-19 fear has become a psychological consequence that increases stress among nursing staffs. This study fills the research gap about the performance of the health care sectors, particularly with respect to COVID-19 fear and COVID-19 stress among nurses. Hence, COVID-19 fear plays a significant role in COVID-19 stress in terms of influencing the health care performance of nurses. Overall, the results give pragmatic insights for the consequences of the COVID-19 pandemic.